Barbadense cotton cultivation (Gossypium barbadense L.), Pima variety of extra-long fiber, for the Brazilian semiarid (Research, Society and Development, 2022)
This work aimed to present the productive and technological results of extra-long fiber produced by producers in Peru, aiming to encourage and expand its cultivation in the Brazilian semiarid region. As it is a proposal for employment and income for the Northeast region, Embrapa Algodão identified important technological processes related to the production system that enhance the yield and improve the quality of cotton Gossypium barbadense breed, whose fiber between 36-38 mm in length can reach a high market price. The American variety Pima-70 would be the most suitable for the Brazilian semiarid region due to its tolerance to warm regions. Based on the results obtained for the cultivar Pima in Peru in rainfed and complementary irrigation conditions, their respective yields ranged from 3,220 to 3,680 Kg/ha (organic production system) and 4,500 Kg/ha (conventional production system with irrigation by flooding), combined with adequate soil preparation and efficient cultural management.